Pemanfaatan Limbah Kain Perca Menjadi Pot Di Desa Keseneng Kabupaten Wonosobo Oleh Wali Murid SD - Tsaniyahtuzzahroh Tsaniyahtuzzahroh; Hafi Sofwan Nadi; Nadim Shidqi Nazuwa; Iman Ahmad Ihsanudin (Jurnal Pengabdian Masyarakat PGSD, 2022)
Waste is one of the environmental problems that are difficult to deal with. Cloth and plastic waste is inorganic waste which is very difficult to decompose, therefore cloth and plastic waste often become an environmental problem because it is still used in large quantities. To avoid these environmental problems, it is necessary to use cloth waste in goods that have use value and are also useful as an alternative to polybags for parents who like to grow crops. Keseneng Village is a village located in Wonosobo Regency. Student parents' awareness of the importance of waste management is still relatively small. Therefore, we, KPM students at the University of Sains Al-Qur'an, Central Java, provided training on the utilization of cloth waste in pots. The implementation method is by experimenting with making pots before being demonstrated, outreach to the public about the use of fabric waste, demonstrations, and practices. The purpose of this training is to raise awareness of the people of Keseneng Village in processing patchwork waste into usable items. By holding this activity, parents' knowledge of the importance of waste management is increasing, especially in processing patchwork waste. This increased knowledge brought parents to be creative in processing patchwork waste where the waste is processed into useful pots.